Advancement of academic communication by use of networked information: a Croatian perspective - Aparac, Tatjana; Vrana, Radovan (2001)
Since the advent of computers there have been many books and articles written about the innovations and importance of IT in many working areas as well as in the home environment. In the last decade, wide- spread use of personal computers and extensive expansion of the Inter- net have caused many changes, including the emergance of a great quantity of published works covering di&iexcl ; ; erent themes related to the de- velopment and use of IT. During that time academic community was almost always the &cent ; ; rst social group analysing the implications and pos- sible use of new technology in research and teaching. Therefore, mem- bers of the academic community were privileged to use new IT, but they were also constantly asked and questioned about its value in theo- retical and practical domain. In that sense, the Croatian academic com- munity is no di&iexcl ; ; erent from any other academic community in the world in terms of development, use and evaluation of computers and computer networks for research and teaching.
Časopis je bio naveden u Pravilniku iz NN 2/97 koji je 2002. godine ukinut.
Projekt MZOS
Projekt MZOS
ENG